Physical Education: Study of different perceptions of students on the concept of Physical Education in First Middle School and Vocational Middle School - Mu'arifin Mu'arifin; Mashud Mashud; Zsolt Nemeth (Graduate School of Universitas Negeri Malang, 2022)
This research aims to measure the truth level of the perception of the students on the physical education concept, and to figure out the difference perception between male and female students at the junior high school and vocational high school levels. Method used is survey with the use of closed inventory questionnaire. This study is conducted on two populations, that are 3700 students of X class at Vocational High School in the Regency of Banyuwangi and 750 students of VIII class at Junior High School in the Regency of Pacitan. Study sample is taken by purposive so that it is obtained 370 vocational high school students and 150 junior high school students. Data analysis technique uses descriptive statistics to figure out the percentage of correct and wrong perception; and to test difference perception between male and female students is used t-Test parametric statistics and Mann Whitney u-Test non-parametric. Research results show that the truth level of the junior high school students’ perception on the education concept is in the very good category, while at the vocational high school level it is in the good category; there is difference perception on students at vocational high school level, while at the junior high school level there is no difference perception.